Blood-Saliva Barrier: Models of its Reproduction - Dyachenko, E.I.; Bel’skaya, L.V. (Biomedical Chemistry: Research and Methods, 2026)
In this review we have summarized existing approaches used to study the blood-saliva barrier in vitro. Investigating the structural and functional characteristics of the blood-saliva barrier in both health and disease requires models that adequately reflect real human physiology. Accordingly, we evaluated currently available research models, such as ex vivo, in vitro (including TR 146, HSY, TEER), oral mucosal equivalents (OME), and in silico systems. To build more accurate in vitro models of the blood-saliva barrier, it is necessary to consider additional parameters. These parameters include the rheological properties of saliva, changes in blood flow and innervation, the state of the immune system, and the oral microbiome. A comprehensive understanding of these components and the characteristics of the blood-saliva barrier is necessary for the development of complex in vitro models.